Introduction to Intellectual Property Rights Protection for Beginner Entrepreneurs in Secondary Education Environments - Darman, Melani; Wardhani, Sri Pramudya; Rahmahani, Adhining Prabawati; Idris, Irda Nuraprida; Ahmad, Ahluddin Saiful (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The development of the business world is no longer solely the domain of adults but is also beginning to be introduced to young people. Several businesses are being started by young people under the age of twenty. This is a very encouraging development and deserves support from all relevant parties. Furthermore, several high schools have begun adding entrepreneurship courses to their curriculum. However, the curriculum certainly does not provide legal knowledge regarding the business world. This leaves a gap that must be filled immediately to prepare aspiring young entrepreneurs to run their businesses. An introduction to the law in starting a business begins with an introduction to intellectual property protection, particularly trademarks and copyrights. These two legal protections are directly related to the business world, both small and large.Purposes of The Devotion: The purpose of this devotion is to provide students with initial knowledge about intellectual property rights and the importance of such protection in the business world.Method of The Devotion: The method used is a presentation of the material followed by a question-and-answer session to provide in-depth understanding. Students are also given pre- and post-tests to gauge their understanding before and after the presentation.Results Main Findings of the Devotion: The results of this community service implementation showed that students were very enthusiastic about listening to the presentation, as indicated by the diverse questions they asked about intellectual property protection. Furthermore, there was an increase in student understanding after being given the presentation on the material.